Analisis Hukum Terhadap Penyertaan Modal Pemerintah Kota Tebing Tinggi Pada PT. Bank Sumut Sebagai Badan Usaha Milik Daerah - Trisna, Dudy Agung (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
The Regional Government Law gives authority to regions to explore regional potential with the aim of prospering the welfare of the local community. One of the regional efforts in realizing prosperity and welfare for the region is through capital participation in regional-owned company (BUMD). This study aims to provide an overview of how the rules and regulations governing local financial capital participation in BUMD companies, and how the process of implementing capital participation by the Tebing Tinggi City Government in the regionally owned company PT. Bank of North Sumatra and what the legal consequences of the Tebing Tinggi City Government's investment in PT. Bank of North Sumatra. This study uses a normative juridical method and uses secondary data, namely primary, secondary and tertiary legal materials and data collection techniques using literature study and field research by means of interviews. The results show that: the existing regional regulations at Pemko Tebing Tinggi regarding equity participation in PT. Bank of North Sumatra is not yet in accordance with existing laws and regulations. Third, the legal consequence of the mismatch between the regulations and the implementation related to capital participation that occurs in Tebing Tinggi City Government, does not result in the cancellation or legal invalidation of the capital participation. This is because the nominal capital participation has been recorded in the respective books Keyword : Investment Participation, Regional Government, Regional Owned Company.